Contemporary History as an Intrusion into Personal Memory: Methodological Dilemmas, Public Presence and the Perils of Presentism. (February 2023) - Hatzivassiliou, Evanthis
Abstract : In a brilliant 1972 cartoon, the creator of Snoopy, Charles M. Schulz, depicts the contemplative beagle going through a crisis of rage. Snoopy discovers that a six-storey parking garage has been built on the site of the Daisy Hill Puppy Farm, a place in which, we are led to understand, he had spent some of his happiest childhood moments. Snoopy cannot contain himself. 'You stupid people', he shouts; 'You're parking on my memories'.